2008
DOI: 10.1029/2008gl034475
|View full text |Cite
|
Sign up to set email alerts
|

Snow anomaly events from historical documents in eastern China during the past two millennia and implication for low‐frequency variability of AO/NAO and PDO

Abstract: Models and instrumental data indicate that the spatial and temporal variations of snow cover are significantly related to atmospheric circulation (e.g. the AO/NAO). Here, we present historical snow anomaly events during the past two millennia that provide a unique temporal window to studying long‐term AO/NAO, a prominent phenomenon in wintertime. Direct descriptions such as “no snow during the winter” and “pray God for snow” are interpreted as convincing evidence for snow anomalies. The variations of positive/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…First, the southward shift of the westerlies and the stronger pole-equator thermal gradient, associated with low temperatures during the LIA, could have resulted in an increase of cyclonic activity over the mid-latitudes and thus more precipitation [57,58] . Second, the predominantly negative NAO winter index during the LIA [59] could have lead to an increase in precipitation at mid-latitudes of continental Asia. This inverse association was suggested by statistical analyses of meteorological data from relevant hydro-climatic stations [60] .…”
Section: Comparison Of Moisture Evolution In the Westerly-dominated Amentioning
confidence: 98%
“…First, the southward shift of the westerlies and the stronger pole-equator thermal gradient, associated with low temperatures during the LIA, could have resulted in an increase of cyclonic activity over the mid-latitudes and thus more precipitation [57,58] . Second, the predominantly negative NAO winter index during the LIA [59] could have lead to an increase in precipitation at mid-latitudes of continental Asia. This inverse association was suggested by statistical analyses of meteorological data from relevant hydro-climatic stations [60] .…”
Section: Comparison Of Moisture Evolution In the Westerly-dominated Amentioning
confidence: 98%
“…to reduce the bias of abundant historical documentation over time (see Chu et al, 2008), where NDA is the number of years with negative drought anomalies per decade, PDA is the number of years with positive drought anomalies per decade, and x represents a threshold which defines the drought anomalies. For IDA 1 , only drought that reached Grade 1 or above would be considered as positive drought anomalies.…”
Section: Overall Relationship Between Nao and Droughtmentioning
confidence: 99%
“…Because previous research showed a significant relationship between atmospheric circulation and the precipitation anomalies over China (Xin et al 2006, Su & Wang 2007, Chu et al 2008, Wei et al 2008, we hypothesized PC2 to be related to atmospheric circulation, and we compared it with some general atmospheric circulation parameters in the Northern Hemisphere for verification. Three atmospheric circulation parameters were selected to investigate their possible influence on PC2 in the GNQR.…”
Section: Comparison Of Pc1 With Population Pressurementioning
confidence: 99%
“…Although much attention has focused on the disasters (flood and drought in particular) in eastern and southern China (Liu et al 2001, Jiang et al 2005, Stige et al 2007, Chu et al 2008, Zhang et al 2008b, 2009, Yin et al 2009), few studies have carefully considered the disasters in northwestern China. This phenomenon may be attributable to the fact that historical documents are less abundant in northwestern China than in eastern and southern China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation